2018
DOI: 10.1093/ejo/cjy065
|View full text |Cite
|
Sign up to set email alerts
|

Long-term stability of curve of Spee levelled with continuous archwires in subjects with different vertical patterns: a retrospective study

Abstract: Objectives:The aim of the study was to evaluate the curve of Spee (COS) stability in patients treated with continuous archwires with different vertical patterns. Methods: The study sample consisted of 60 patients (28 males, 32 females; mean age 19.8 ± 1.4 years) presenting with COS depth of at least2 mm at baseline. For each subject, lateral cephalograms and dental casts were available before treatment (T1), at the end of orthodontic therapy (T2), and 2 years after the end of treatment (T3). All subjects were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…[ 3 ] Studies recently suggested utilizing pharmacologic therapy, biomaterial, and the chewing force in an attempt to provide another mechanism to enhance the stability of teeth after orthodontic treatment. [ 4 5 6 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 ] Studies recently suggested utilizing pharmacologic therapy, biomaterial, and the chewing force in an attempt to provide another mechanism to enhance the stability of teeth after orthodontic treatment. [ 4 5 6 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…One of the dependable methods used for flatting of the COS—that recommended by Andrews 1972[ 15 ] is the extrusion of the infra erupted premolars to be in a flat plane with the incisors by the straight wire appliance,[ 38 ] this method was used to acquire a more stable orthodontic outcome. [ 1 39 40 ]…”
Section: Discussionmentioning
confidence: 99%
“…As an extremely strong muscleocclusion-joint triangular balance is too robust to be broken and reconstructed, it is hard for short-faced people to reestablish a new physiological homeostasis of the masticatory complex, indicating that occlusal treatment for these patients is awfully tough [29,30]. For example, it is generally rather difficult to increase the vertical height or open bite in occlusal therapy due to the powerful muscle-occlusion balance, and the curative effect is unstable with a high recurrence rate [31,32]. Moreover, these patients usually have a stout jaw and high bone density [21], which poses a challenge for successful tooth movement in orthodontic treatment, especially in cases of tooth extraction.…”
Section: Introductionmentioning
confidence: 99%